2021
DOI: 10.31234/osf.io/mrp6v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redefining Groove

Abstract: Groove is a popular and widely-used concept in the field of music. Yet its precise definition remains elusive. Upon closer inspection, groove appears to be used as an umbrella term with various connotations depending on the musical era, the musical context, and the individual using the term. Our aim in this paper was to explore different definitions and connotations of the term groove so as to reach a more detailed understanding of it. Consequently, in an online survey, 88 participants provided free-text descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…In the field of musicology, the term groove was coined in the context of African-American musical genres, such as R&B, jazz, soul, disco, funk, and hip-hop, where it can refer to esthetic qualities of the music, specific rhythmic patterns, or the musicians’ way of effortlessly synchronizing and interacting with each other ( Senn et al, 2019 ; Câmara and Danielsen, 2020 ; Duman et al, 2021 ). In contrast to this multifaceted understanding, recent studies in music perception and cognition agree on a sharper definition of groove as the pleasurable urge to move one’s body in relation to the rhythm of music ( Madison, 2006 ; Janata et al, 2012 ; Stupacher et al, 2013 ; Senn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of musicology, the term groove was coined in the context of African-American musical genres, such as R&B, jazz, soul, disco, funk, and hip-hop, where it can refer to esthetic qualities of the music, specific rhythmic patterns, or the musicians’ way of effortlessly synchronizing and interacting with each other ( Senn et al, 2019 ; Câmara and Danielsen, 2020 ; Duman et al, 2021 ). In contrast to this multifaceted understanding, recent studies in music perception and cognition agree on a sharper definition of groove as the pleasurable urge to move one’s body in relation to the rhythm of music ( Madison, 2006 ; Janata et al, 2012 ; Stupacher et al, 2013 ; Senn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The popular musical term, groove, commonly understood as a pleasurable desire to move to music [15] has recently been more comprehensively described as a multifaceted participatory experience [16]. More specifically, Duman and colleagues [16] argue that an experience of groove is not only connected with movement and positive affect but also associated with sensations of immersion and social connectedness shaped by a delicate interaction of specific music-performance-, and individual difference-related variables. Previous groove literature reported several intra-and extra-musical variables relate to groove experience.…”
Section: Music Listening As An Immersive Affective Movement-inducing ...mentioning
confidence: 99%
“…Survey 1. Data were gathered as part of the online listening survey described in Duman et al [16]. For the present study, participants rated their general music listening habits using a questionnaire containing 21 RL items.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…However, even within these genres and within the field of musicology, groove can have different meanings; the term may refer to a repetitive multi-layered pattern of pitch and rhythm (Zbikowski, 2004), the engagement of synchronized body movements arising from such repetitive patterns (Pressing, 2002;Zbikowski, 2004), or the seemingly effortless interactions and 'negotiations' of expressive timing between musicians in a band (Keil, 1995). All of these definitions can be categorized into two dimensions: an objective dimension of structured sounds and a subjective, experienced, phenomenological dimension (Duman et al, 2021).…”
mentioning
confidence: 99%
“…Recent studies suggest that the mere juxtaposition of objective musical causes and subjective psychological effects may be too simplistic to fully capture the groove phenomenon. Studies have shown that the groove experience is moderated by the personal background of the listener, such as their musical taste or familiarity with the repertoire (Senn et al, 2021), by the concrete listening situation, such as live vs. recorded music (Swarbrick et al, 2019), and by feelings of social connectedness, immersion, flow, and energetic arousal (Dotov et al, 2021;Duman et al, 2021Duman et al, , 2022Kowalewski et al, 2020;Stupacher, 2019;Senn et al, in press), indicating that the groove experience is complex and multifaceted (Senn et al, 2019).…”
mentioning
confidence: 99%